PERTUNJUKAN IMAM SHOLAT DAN TAFSIR POLITIK JAMAAH - Rohim, Syaiful (Universitas Islam Negeri Raden Intan Lampung, 2014)
PRAYER LEADER AND THE INTERPRETATION OF POLITICAL CONGREGATION. Being a religious leader is not dissimilar to being a social leader. Besides he has to perform religius duties personally, he also received an additional task to carry out the functions of religious leadership in accordance with the social capacity he has in his social group. In the social space, ritual practices are actually not dissimilar to other social behavior, especially in the process of interaction and subjective meanings of symbols. When a person is interacting, the behavior that he played in performing religious rituals- for example became a prayer leader - actually remains in the frame of “interaction order” to meet the “self-perfection”. This article reviewed the symbolic meaning of leadership in the practice of prayer. By using interpretative paradigm of Lindlof in the phenomenological research tradition, the authors classify the prayer leadership typology based on specific symbols and behavior, namely: “conditional compromise leader”, “Image-Sensational leader”, “autonomus leader”, and “Ideal-literalists leader”.